Do your employees think your slogan is "fake news?" A framework for understanding the impact of fake company slogans on employees. Issue 2 (26th June 2019) - Lee, Linda W.; Hannah, David; McCarthy, Ian P.
Abstract : Purpose: This article explores how employees can perceive and be impacted by the fakeness of their company slogans. Design/methodology/approach: This conceptual study draws on the established literature on company slogans, employee audiences, and fake news to create a framework through which to understand fake company slogans. Findings: Employees attend to two important dimensions of slogans: whether they accurately reflect a company's (1) values and (2) value proposition. These dimensions combine to form a typology of four ways in which employees can perceive their company's slogans: namely, authentic, narcissistic, foreign, or corrupt. Research limitations/implications: This paper outlines how the typology provides a theoretical basis for more refined empirical research on how company slogans influence a key stakeholder: their employees. Future research could test the arguments about how certain characteristics of slogans are more or less likely to cause employees to conclude that slogans are fake news. Those conclusions will, in turn, have implications for the morale and engagement of employees. The ideas herein can also enable a more comprehensive assessment of the impact of slogans. Practical implications: Employees can view three types of slogans as fake news (narcissistic, foreign, and corrupt slogans). This paper identifies the implications of each type and explains how companies can go about developing authentic slogans. Originality/value: This paper explores the impact of slogan fakeness on employees: an important audience that has been neglected by studies to date. Thus, the insights and implications specific to this internal stakeholder are novel.